SOSIALISASI KEWIRAUSAHAAN DI SMP NEGERI 01 KECAMATAN GUNUANG OMEH KABUPATEN LIMA PULUH KOTA - Weriantoni Weriantoni; Hanifatul Huda (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Nagari Kototitinggi is one of the villages in Gunung Omeh Subdistrict, Lima Puluh Kota District, which consists of 8 jorong areas. In this Nagari. There is only one junior high school, namely SMP Negeri 01 Gunung Omeh sub-district. Here I see so much potential from adolescents that can be empowered so that later it can be useful and contribute significantly to society and the region because of the large number of teenagers there. I also see the potential of this region in Nagari Kototinggi that can be managed, so I made a work program about this entrepreneurship. Under the theme of KKN PPM Andalas University in 2019, "Technology Implementation To Achieve Nagari Independence", then in addition to providing business motivation and necessary foundations in entrepreneurship, these school children are also given about ways on how they can utilize the technology that is developing at this time to use for more useful activities, not just for playing, but can be used for entrepreneurship that will also benefit them. The method used in this work program was in the form of socialization in the form of providing education with power points on the basics of entrepreneurship and, interspersed with motivational videos and motivational words for entrepreneurship and at the end of the time held questions and answers and discussions. With this socialization is expected to grow souls Entrepreneurs from the beginning to adolescents in Nagari Koto Tinggi, and later they can apply this to their lives because this entrepreneurial spirit is essential for the creation of entrepreneurs who can contribute and build the economy around them.